Daily life in ancient Egypt : recreating Lahun - Szpakowska, Kasia Maria (Malden, MA : Blackwell Pub., 2008)
Using the life of a young girl and her family as a model, this book recreates the daily life of the middle-class residents of the ancient town of Lahun during Egypt's Middle Kingdom period. This perfect snapshot in time has been painstakingly recreated using recently published textual data and archaeological findings. Provides an illuminating and engaging re-construction of what daily life was like in ancient Egypt. Describes the main issues of everyday life in the town - from education, work, and food preparation to religious rituals, healing techniques, marriages, births, and deaths. Authentically recreated through the use of recently published textual data and archaeological findings directly from the settlement of Lahun and other sites. Includes photographs and illustrations of actual artifacts from the settlement of Lahun.
The setting -- Birth -- Close to home -- The stuff of life -- Crafts and trades -- Learning, earning, and leisure -- Religion -- Sickness -- Death -- Love.
Includes bibliographical references (p. 225-238) and index.
Keywords: Egypt -- Antiquities; Egypt -- Social life and customs -- To 332 B.C.; Kahun (Extinct city)